Analysis of the Influence of Sustainability Reporting on Company Market Performance - Arif Mulyono; Murtanto (Dinasti Publisher, 2025)
This study aims to analyze the impact of economic, environmental, and social performance disclosures in sustainability reports on market performance in the food and beverage sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Using an explanatory research method, the data were analyzed through a multiple linear regression approach. The independent variables include economic, environmental, and social performance disclosure indices measured based on GRI 2021 standards, while market performance is proxied by the Tobin's Q ratio. The results indicate that, simultaneously, economic, environmental, and social performance disclosures do not significantly affect market performance. These findings differ from previous studies, possibly due to the unique characteristics of the food and beverage sector, which primarily produces consumer staples where factors such as consumer perception and economic conditions are more dominant. This study is expected to provide insights for companies, investors, and policymakers on the importance of considering sustainability factors in business strategies and their implications for market outcomes.